CONDUCTIVITY OF THERMOTROPIC IONIC LIQUID CRYSTALS - Gridyakina, Aleksandra (Proceedings of National Aviation University (archive), 2015)
The article represents the results of electrical conductivity studies of cobalt decanoate and lead decanoate oriented samples. It was determined that samples are weak electrolytes in the liquid crystal state region. The samples are characterized by great anisotropy of bulk conductivity caused by molecular order.